Phanerochaete chrysosporium β-Glucosidases: Induction, Cellular Localization, and Physical Characterization - Smith, Mark H. (1979)
Phanerochaete chrysosporium produces intracellular soluble and particulate β-glucosidases and an extracellular β-glucosidase. The extracellular enzyme is induced by cellulose but repressed in the presence of glucose. The molecular weight of this enzyme is 90,000. The K(m) for p-nitrophenyl-β-glucoside is 1.6 × 10(−4) M; the K(i) for glucose, a competitive inhibitor, is 5.0 × 10(−4) M. The K(m) for cellobiose is 5.3 × 10(−4) M. The intracellular soluble enzyme is induced by cellobiose; this induction is prevented by cycloheximide. The presence of 300 mM glucose in the medium, however, had no effect on induction. The K(m) for p-nitrophenyl-β-glucoside is 1.1 × 10(−4) M. The molecular weight of this enzyme is ∼410,000. Both enzymes have an optimal temperature of 45°C and an E(act) of 9.15 kcal (ca. 3.83 × 10(4) J). The pH optima, however, were ∼7.0 and 5.5 for the intracellular and extracellular enzymes, respectively.